Hak dan Kebutuhan Dasar Penyandang Disabilitas di dalam Al-Quran - Ridho Riyadi; M. Adin Setyawan; Khoirul Wahyu Wahidatun (Studia Quranika, 2022)
The purpose of this study is to investigate the Qur'anic concept of disabled people's rights and needs. By returning to the Qur'anic writings that explain their existence, It can be shown that these texts actually pertain to the notion of protection as in the letter Abasa: 1-2, rather than oppression and bullying. From this, it is clear that the Qur'an considers all human degrees to be equal before God, with the sole difference between a person's degree with Allah being on the side of piety. This is a library study that employs a Descriptive-analytical technique. According to the findings According to the findings, the rights and needs of people with disabilities in the In the Qur’an; The first, acknowledging their existence; second, equal treatment of people with disabilities; The third access to services for people with disabilities; fourth, empowering people with disabilities who have the same potential and abilities as normal people; fifth, equal justice under the law; sixth, religious; and seventh, communication and information.